A review of electrochemical impedance spectroscopy for bioanalytical sensors. Issue 45 (7th November 2022) - Randviir, Edward P.; Banks, Craig E.
Abstract : EIS is mainly employed for immunosensors and aptasensors, but opportunities exist for enzymatic, composite and other sensor strategies. Abstract : Electrochemical impedance spectroscopy (EIS) is a powerful technique for both quantitative and qualitative analysis. This review uses a systematic approach to examine how electrodes are tailored for use in EIS-based applications, describing the chemistries involved in sensor design, and discusses trends in the use of bio-based and non-bio-based electrodes. The review finds that immunosensors are the most prevalent sensor strategy that employs EIS as a quantification technique for target species. The review also finds that bio-based electrodes, though capable of detecting small molecules, are most applicable for the detection of complex molecules. Non-bio-based sensors are more often employed for simpler molecules and less often have applications for complex systems. We surmise that EIS has advanced in terms of electrode designs since our last review on the subject, although there are still inconsistencies in terms of equivalent circuit modelling for some sensor types. Removal of ambiguity from equivalent circuit models may help advance EIS as a choice detection method, allowing for lower limits of detection than traditional electrochemical methods such as voltammetry or amperometry.